Differential susceptibility of distinct parts of the aquatic plant Nymphoides humboldtiana to herbivory supports the optimal defense theory. Issue 11 (15th November 2021) - Nocchi, Nathália; Pereira, Renato C.; Duarte, Heitor M.; Clavico, Etiene E. G.; Konno, Tatiana U. P.; Soares, Angélica R.
Abstract: Premise: The optimal defense theory (ODT) predicts that the allocation of chemical defenses in plants will be concentrated in parts or tissues that are of higher fitness value for the individuals that produce them. Chemicals are known to be allocated to certain parts of aquatic plants, and the morphological architecture of Nymphoides humboldtiana, a species that exposes its parts to different environmental factors and consumers, may be an excellent model to evaluate within‐plant susceptibility to consumers according to the ODT. Methods: Under laboratory experimental conditions, we evaluated the defensive properties of extracts from vegetative (leaves, rhizomes, roots) and reproductive (long stem internodes, flowers, fruits) parts of N. humboldtiana against consumption by the generalist herbivorous gastropod Biomphalaria glabrata . Extracts were also subjected to chemical analysis by high‐performance liquid chromatography, principal component analysis, and analysis of their relationships to defensive actions. Results: Extracts of all vegetative and internode (reproductive) parts of N. humboldtiana exhibited defensive properties against B. glabrata, but the long stem internodes exhibited the highest percentage of inhibition. Chemical profiles of these parts were qualitatively and quantitatively different, but a major unidentified compound is presumably responsible for the higher defensive property found in internodes. Conclusions: Our results support the ODT, since chemical defense was more effective in long stem internodes, which have a high fitness value for N. humboldtiana to keep the flowers emerged on the water surface in response to the rapid and dynamic changes in water levels typical of freshwater environments.